2018
DOI: 10.1080/08869634.2018.1444537
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorders and mandibular vertical asymmetry

Abstract: Objective To analyze the association between mandibular vertical asymmetry and the presence of TMD in adult patients. Methods This case-control study recruited patients from the orthodontic clinic at FEBUAP. Patients were classified on the basis of diagnostic criteria for temporomandibular disorders (DC/TMD). Panoramic radiographs were measured to determine mandibular vertical asymmetry indices according to criteria described by Kjellberg and Habets. Both methods (DC/TMD and index criteria) were standardized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
6
0
5
Order By: Relevance
“…Patients with skeletal Class III malocclusion and mandibular deviation have different condylar morphology in their DS and NDS, although the overall volume of the TMJ space is practically the same 22–24 . In this group of patients, orthognathic surgery increases TMJ space volume, and the change is correlated with the degree of deviation as the postoperative period lengthens.…”
Section: Discussionmentioning
confidence: 96%
“…Patients with skeletal Class III malocclusion and mandibular deviation have different condylar morphology in their DS and NDS, although the overall volume of the TMJ space is practically the same 22–24 . In this group of patients, orthognathic surgery increases TMJ space volume, and the change is correlated with the degree of deviation as the postoperative period lengthens.…”
Section: Discussionmentioning
confidence: 96%
“…24 An accurate diagnosis of the presence of asymmetry in the mandibular facial third is important for clinicians to achieve a harmonious and balanced facial appearance following orthodontic, surgical or combined treatment options. In past studies, mandibular asymmetry has been detected by applying an asymmetry index formula introduced by Habets et al 6,11,[17][18][19][20]22 Mandibular vertical asymmetry was evaluated using this formula in patients who presented with temporomandibular disorders, 15 Class I, Class II and Class III malocclusions 6,17,18 and unilateral and bilateral posterior crossbites. [19][20][21] Although the formula uses vertical dimensional measurements of the condyle and the rami and determines mandibular vertical asymmetry, the present study is the first to investigate mandibular vertical asymmetry on panoramic radiographs, in patients of different vertical skeletal patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In later studies, it was concluded that vertical measurements of the height of the condyle or ramus could be reliably assessed on panoramic images with acceptable reproducibility. 10,[12][13][14] The Habets method has been used to evaluate vertical mandibular asymmetry in temporomandibular disorders, 15,16 Class I, Class II and Class III malocclusions, 6,17,18 unilateral and bilateral posterior crossbites [19][20][21] and different sagittal skeletal patterns. 22 However, controversial findings have been reported…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetry of the mandible is a potential cause of dysfunction of the mandible and TMJ as a bilateral joint. Numerous studies have explored the association of vertical asymmetry of the condyle with the risk of TMJ disc displacement ( 10 - 16 ).…”
Section: Introductionmentioning
confidence: 99%